2014
DOI: 10.1007/s11356-014-3915-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dermal absorption of DEET-containing insect repellent and oxybenzone-containing sunscreen using human urinary metabolites

Abstract: Mutual enhancement of dermal absorption of N,N-diethyl-m-toluamide (DEET) and oxybenzone (OBZ) has been reported recently with DEET and OBZ being active ingredients of insect repellent and sunscreen, respectively. To assess the reported enhancing effect directly, we used human urinary metabolites as biomarkers; besides, we also sought to determine the best way for concurrent use of these two products without extra absorption of either. Four dermal application methods were used: DEET only (S1), OBZ only (S2), D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Skincare products contain various components, like surfactants, alcohols, polyols, and essential oils which can affect the barrier function of the stratum corneum and function as chemical permeation enhancers [ 44 ]. Pont et al [ 45 ] showed that the dermal penetration of a herbicide, 2,4-dichlorophenoxyacetic acid through hairless mouse skin in 24 h increased from 54.9 ± 4.7% to 86.9 ± 2.5% in the presence of padimate-o-containing sunscreen, while Wang and Gu [ 46 ] and Yiin et al [ 47 ] demonstrated that the use of sunscreen, oxybenzone after application of a repellent, and DEET (N,N-diethyl-m-toluamide) increases the absorption of DEET through human skin. Along with these studies, our results corroborate that caution shall be given to the concurrent uses of cosmetics and potentially toxic chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…Skincare products contain various components, like surfactants, alcohols, polyols, and essential oils which can affect the barrier function of the stratum corneum and function as chemical permeation enhancers [ 44 ]. Pont et al [ 45 ] showed that the dermal penetration of a herbicide, 2,4-dichlorophenoxyacetic acid through hairless mouse skin in 24 h increased from 54.9 ± 4.7% to 86.9 ± 2.5% in the presence of padimate-o-containing sunscreen, while Wang and Gu [ 46 ] and Yiin et al [ 47 ] demonstrated that the use of sunscreen, oxybenzone after application of a repellent, and DEET (N,N-diethyl-m-toluamide) increases the absorption of DEET through human skin. Along with these studies, our results corroborate that caution shall be given to the concurrent uses of cosmetics and potentially toxic chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…We used three time difference scenarios for the data to compare urine samples in the equivalent stage of metabolism and excretion of a given insect repellent application. The shortest time interval examined in previous studies was 2 to 4 hours ([ 6 ]—human plasma 2 hours, urine 4 hours), ([ 25 ]—human urine, selected 4 hour compartments), ([ 26 ]—human urine 4 hours), which led to the choice of investigating a lag time of 0, 2 and 4 hours. The processes for the excretion of DEET metabolites in urine appear to require at least a short time lag between application and excretion [ 6 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The shortest time interval examined in previous studies was 2 to 4 hours ([ 6 ]—human plasma 2 hours, urine 4 hours), ([ 25 ]—human urine, selected 4 hour compartments), ([ 26 ]—human urine 4 hours), which led to the choice of investigating a lag time of 0, 2 and 4 hours. The processes for the excretion of DEET metabolites in urine appear to require at least a short time lag between application and excretion [ 6 , 25 , 26 ]. The analysis of a zero lag time was included to take into account the possibility of immediate excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Despite inclusion in malaria prevention programs, both chemicals have known associated dangers (Diaz, 2016). DEET is known to have heightened toxicity when applied with sunscreen (Yiin, Tian & Hung, 2015; Rodriguez & Maibach, 2016), a situation likely to arise for military personnel deployed to tropical and subtropical regions of the world. Additionally, synergism has been observed during simultaneous exposure to DEET and permethrin, leading to neuronal degeneration and significant neurobehavioral effects (Abdel-Rahman et al., 2004).…”
Section: Introductionmentioning
confidence: 99%